EFEKTIVITAS PROGRAM REHABILITASI SOSIAL GELANDANGAN DAN PENGEMIS DI KOTA BATAM - Rasyid, Muhammad; Dompak, Timbul (SCIENTIA JOURNAL, 2022)
The presence of homeless and beggars is not only an eyesore, but also disturbs public order and their presence also violates the government's policy on areas free from homeless people and beggars as regulated in Batam City Regional Regulation Number 6 of 2002 concerning Social Order in Batam City. Social Rehabilitation carried out by the Batam City Social Service and Community Empowerment is a breakthrough made by the government in eradicating the problem of homeless people and beggars in Batam City. The research aims to analyze the effectiveness of the Social Rehabilitation of the homeless and beggars in Batam City and to analyze the supporting and inhibiting factors of the Social Rehabilitation of the homeless and beggars in Batam City. This study uses a qualitative method with a descriptive approach. The results of this study can be concluded that the effectiveness of the social rehabilitation program for homeless beggars in the city of Batam has been running quite well but in its implementation there are several obstacles such as lack of communication, resources. It is hoped that by knowing these weak sides, it must be addressed as soon as possible so that the social rehabilitation program can run well.